Kistik fibrozis-dışı bronşektazili çocukların hayat kalitesi ve sosyoekonomik seviyesi araştırması - Hamzah, Ameer (My University, 2011)
Bronşektazi gelişmekte olan ülkelerde hala önemli bir hastalıktır. Bu çalışmanın amacı kistik fibrozis dışı bronşektazili çocuklarda yaşam kalitesini ve ilişkili faktörleri araştırmaktı. Çalışmaya Marmara Üniversitesi Çocuk Göğüs Hastalıkları polikliniğinde izlenen 47 kistik fibrozis dışı bronşektazili çocuk alındı. Semptomların başlangıç yaşı, sıklığı, tanı yaşı, hastaların fizik muayene bulguları, solunum fonksiyon testleri (SFT), antibiyotik kullanım sayısı ve yüksek rezolüsyonlu bilgisayarlı tomografide (YRBT) etkilenen loblar değerlendirildi; ayrıca YRBT bulguları bronşektazi yaygınlık derecesini saptamak üzere modifiye Bhalla skorlama sistemine göre skorlandı. Sosyoekonomik seviye (SES) formu, hayat kalitesini saptamak amacıyla St. George Solunum Anketi (SGRQ) ve Yaşam Kalitesi kısa form 36 (SF-36) dolduruldu. Hastaların 23'ü (% 48,9) erkekti, yaş ortalaması 12,10 ± 3,02 yıl, tanı yaşı ortalaması 7,31 ± 3,32 yıl, şikayet yaşı ortalaması 3,05 ± 3,33 yıl olarak bulundu. Takip süresi ortalaması ise 3,64 ± 2,45 yıl olarak saptandı. SGRQ semptom skoru ile takip süresi arasında negatif anlamlı ilişki bulundu (p<0,05). SGRQ, SF-36 ve SFT arasında anlamlı ilişki bulundu (p<0,05). Antibiyotik kullanım sayısıyla SGRQ semptom ve SF36 fizik skoru arasında

Bronchiectasis is still an important problem in developing countries. The aim of this study was to evaluate the health-related quality of life and associated factors in children with non-cystic fibrosis bronchiectasis. Children with non–cystic fibrosis bronchiectasis followed at Marmara University Paediatric Pulmonology Clinic were included to the study. Age of symptom onset, age of diagnosis, frequency of presenting symptoms, physical examination findings, pulmonary function tests, antibiotic therapy in acute exacerbations, affected lobes in high resolution computed tomography (HRCT) were evaluated; in addition, HRCT was scored according to modified Bhalla score system to obtain a bronchiectasis distribution severity score. St George‟s Respiratory Questionnaire (SGRQ), the Medical Outcomes Study Short Form-36 and socioeconomic status questionnaires were completed by patients and parents. The mean age of the patients (48.9% male) was 12,10 ± 3,02 years. The mean age at diagnosis was 7,31 ± 3,32 years and follow up period was 3,64 ± 2,45 years. There was a negative correlation between follow up period and SGRQ scores (p<0,05). Patients with worse pulmonary function tests (PFT) had worse quality of life according to SGRQ and SF-36. Frequency of antibiotic therapy has significant correlation with SGRQ symptom component and SF-36 physical component (p<0,05). There was a greater delay in diagnosis in patients with lower socioeconomic status (p<0,05). Patients with worse pulmonary functions have lower quality of life scores. Early diagnosis and treatment may increase the quality of life and survival of patients with bronchiectasis, which has irreversible and progressive complications if untreated.
Keywords: Çocuk Sağlığı ve Hastalıkları; Yaşam Kalitesi